National budget for 1971: Finland (Helsinki: Ministry of Finance Economic Department, 1971)
The Economic Survey published as an appendix to the Government's budget proposal for 1971 included forecasts concerning economic developments in 1971.
osc 21/05/2019
Loans
Keywords: Budgets; Expenditure, public; Finland